Empathy, Altruism, and Group Identification - Miyazono, Kengo; Inarimori, Kiichi (Frontiers in Psychology, 2021)
This paper investigates the role of group identification in empathic emotion and its behavioral consequences. Our central idea is that group identification is the key to understanding the process in which empathic emotion causes helping behavior. Empathic emotion causes helping behavior because it involves group identification, which motivates helping behavior toward other members. This paper focuses on a hypothesis, which we call “self-other merging hypothesis (SMH),” according to which empathy-induced helping behavior is due to the “merging” between the helping agent and the helped agent. We argue that SMH should be interpreted in terms of group identification. The group identification interpretation of SMH is both behaviorally adequate (i.e., successfully predicts and explains the helping behavior in the experimental settings) and psychologically plausible (i.e., does not posit psychologically unrealistic beliefs, desires, etc.). Empathy-induced helping behavior, according to the group identification interpretation of the SMH, does not fit comfortably into the traditional egoism/altruism dichotomy. We thus propose a new taxonomy according to which empathy-induced helping behavior is both altruistic at the individual level and egoistic at the group level.